Pemanfaatan Buah Pepaya California Dalam Modifikasi Pembuatan Kue Bolu Di Desa Carawali Kabupaten Sidrap - Rukmelia Rukmelia; Iranita Haryono; Astrini Padapi; Astrina Nur Inayah; Rifni Nikmat Syarifuddin; Damayanti Trisnasari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Carawali village is an agro-tourism village with wide stretches of rice fields. Seeing this potential, businesses need to optimize their land resources and produce high productivity. California papaya fruit (Carica papaya L) is one type of fruit that has a high selling value. The potential for California papaya is large enough to be developed to increase the amount of public consumption so that it will have an impact on economic growth in the area. Besides having a high selling value, California papaya also has many benefits. Processed papaya products need to be developed so that papaya farmers can also become processors of papaya products, so that their level of economic welfare increases. One of the processed papaya products that can be developed is unyil cake and jam. The research method includes counseling on California papaya business opportunities and training on making unyil cakes and papaya jam. This counseling and training provides a new understanding for the Carawali village community in developing businesses that can provide additional income